Impact of daily administration of teriparatide on the histological pattern of testicular structure in adult male rats - Omar Ameen; Ghada Taqa (Medicinski glasnik, 2026)
Aim: Teriparatide, a synthetic analog of the active fragment of human parathyroid hormone (PTH 1-34), is a clinically approved anabolic treatment for osteoporosis. While its bone-forming capacity is well-documented, evidence regarding its systemic safety, particularly in relation to male reproductive health, remains limited. Aim: This study was designed to investigate the histological consequences of prolonged teriparatide exposure on testicular architecture in adult male rats, addressing a critical gap in its toxicological profile. Methods: Twenty adult male albino rats were randomly allocated into two groups. The control group received subcutaneous saline (1 mL/kg/day), while and the treated group was administered teriparatide (10 µg/kg/day) daily for 60 days. Testes were collected post-euthanasia, fixed in formalin, and processed for histological examination. Spermatogenic activity was assessed using Johnsen’s scoring system, and morphometric parameters, including seminiferous tubule diameter and epithelial height, were quantified. Statistical significance was determined using the Mann-Whitney U test (p?0.05). Results: Histological findings revealed preserved cytoarchitecture with active spermatogenesis in control testes. The teriparatide-treated group exhibited significant degenerative changes, including epithelial detachment, interstitial edema, vascular congestion, and Leydig cell necrosis. Johnsen’s scores were significantly reduced in the treated group (median = 4.5; IQR=1.5) compared to controls (median = 8.0; IQR=2.0; p<0.001). Furthermore, Seminiferous tubule diameter and epithelial height were markedly decreased in the treated animals. Conclusion: The findings suggest that prolonged teriparatide exposure may impair permatogenesis and alter testicular structure. Re-evaluation of its reproductive safety is warranted, particularly for males of reproductive age.
Keywords: teriparatide; Testis; Spermatogenesis; histopathology; Reproductive Toxicity; Johnsen Score.